Cegah dan Kendalikan Hipertensi dengan Tepat untuk Hidup Lebih Lama - Afiatun Nisa, Salsa Zahra; Puadah, Farha Tsamrotul; Amalia, Keila Rahma; Wati Dewi , Neng Mirna; Monika, Dhea; J K, Ridho Boodie; Reiza Putri , Syakila Syalsa; Aprilia, Cici; Heryani, Heni (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2024)
Introduction: Non-communicable diseases (NCDs) are a major global health threat, contributing to over 36 million deaths annually. Hypertension, a key NCD, is associated with poor health outcomes, including reduced quality of life and increased mortality. This community service is carried out with a prevention strategy as an effort to overcome problems through health education. Health education is not only useful in increasing knowledge but has the potential to change a person's behavior in the long run. Objective: The purpose of this service was to increase public knowledge about hypertension prevention and management to encourage healthy lifestyle practices that reduce the prevalence of hypertension. Method: This public service was conducted at Madrasah At-Thohariyah, Kampung Salaksa, Tasikmalaya, Indonesia, on December 8, 2024. The activities included pre-test and post-test assessments, lectures, discussions, and leaflet distribution to educate participants on hypertension, its risks, and prevention methods. Result: A significant increase in participants' knowledge was evaluated through pre-test and post-test with the percentage of individuals in the good knowledge category increasing from 37.5% (pre-test) to 68.75% (post-test). This increase in knowledge demonstrates the effectiveness of the combination of lectures and leaflets in delivering health education. The positive impact arising from the implementation of community service is clear evidence of the success and achievement of goals. Conclusion: Community education on hypertension through engaging and accessible methods can effectively enhance public awareness and promote behavior changes to prevent and control hypertension.